Studies on the acetylating capacity of human colonic epithelial cells for 5-aminosalicylic acid. - Ireland, A; Priddle, J; Jewell, D (Informa Healthcare, 1988)
Following oral administration of sulphasalazine, 5-aminosalicylic acid (5-ASA) is present in serum at very low concentrations and is mostly in the acetylated form. Analysis of rectal mucosal biopsies from patients on sulphasalazine maintenance therapy has shown that the predominant metabolite present is N-acetyl ASA (Clin Sci 1987: 72; 79P). The authors have now investigated whether this acetylation takes place in the epithelium. Isolated colonic epithelial cell suspensions were prepared in Krebs-Henseleit saline from fresh human resection specimens by EDTA digestion and mechanical disaggregation. Cell suspensions remained viable, as determined by lactate production, over 3 hours. Aliquots of cell suspension were incubated with 5-ASA, 0.1 mM, and glucose, 5 mM, at 37°C for 1 or 2 hours. Following incubation, the supernatant was analysed by high performance liquid chromatography for the presence of acetyl-ASA. Following washing, the cell pellet was disrupted ultrasonically, and intracellular acetyl-ASA was also measured. Production of acetyl-ASA in 1 hour was 112.5 (+27 SD) nmol/g dry weight (extracellular) and 48 (+15.6 SD) nmol/g dry weight (intracellular). No intracellular 5-ASA was detected, suggesting rapid and complete acetylation. A cytosolic fraction of the epithelial cells was prepared by centrifugation of homogenized cells at 13,000 g. In the presence of 5-ASA and acetyl-CoA, this enzyme solution produced acetyl-ASA linearly at a rate of 37 nmol/minutes/ mg protein. No acetyltransferase activity was found in the brush border. The cytosol was further purified by passing it through a Superose 12 gel filtration column. Maximum acetyltransferase activity was found in the fraction corresponding to a molecular weight of approximately 30,000. Thus, the human colonic epithelial cell is probably the primary site of acetylation of 5-ASA, and the N-acetyltransferase activity is found in the cytosol. © 1988 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.